Functional characterization of a histone H2A derived antimicrobial peptide HARRIOTTIN-1 from sicklefin chimaera, Neoharriotta pinnata. (January 2023) - Sathyan, Naveen; Muhammed Musthafa, S.; Anju, M.V.; Archana, K.; Athira, P.P.; Prathap, Namitha; Chaithanya, E.R.; Priyaja, P.; Bright Singh, I.S.; Philip, Rosamma
Abstract: Antimicrobial peptides (AMPs) are gene encoded short peptides which play an important role in the innate immunity of almost all living organisms ranging from bacteria to mammals. Histones play a very important role in defense as precursors to bioactive peptides. The present study is an attempt to decipher the antimicrobial activity of a histone H2A derived peptide, Harriottin-1 from sicklefin chimaera, Neoharriotta pinnata . Analysis in silico predicted the molecule with potent antibacterial and anticancer property. The Harriottin-1 was recombinantly produced and the recombinant peptide rHar-1 demonstrated potent antibacterial activity at 25 μM besides anticancer activity . The study strongly suggests the importance of histone H2A derived peptides as a model for the design and synthesis of potent peptide drugs. Highlights: Harriottin-1 is predicted to have antibacterial, anti-inflammatory and anticancer property by in silico analysis. MIC of Harriottin-1 for S. aureus, A.hydrophila, V. cholera and V. fluvialis was found to be 25 μM. Mode of action of Harriottin-1 was found to be cell membrane pore formation and DNA binding.